State Commissioner - Boucherikha, Amar (Journal of Human Sciences, 2022)
State commissioner of council of state, administrative tribunals and conflicts tribunal was born with creation of these jurisdictions under their constitutional texts respective, the organic law n°98-01 of May 30th 1998, amended and completed by the organic law n°11-13 of July 26th 2011, the law n°98-02 of May 30th 1998, and the organic n°98-03 of June 3th 1998. Beyond the “ crisis of youth” which would plead in its favor, the institution is facing a double crisis of real legitimacy and identity therefore it can’t break free of perversion design as a public prosecutor, upstream by texts and downstream and its own reductive design requisitions replace doctrine creating conclusions reduced to final demand ( annulment, reject …)